285 DEVELOPING A FRAILTY CARE PATHWAY IN A REHABILITATION HOSPITAL: A PILOT STUDY. (25th October 2022) - Murphy, J; Webster, C
Abstract: Background: Frailty is a common condition in older adults. The Clinical Frailty Scale (CFS) is a widely used frailty screening-tool within the Irish healthcare system due to its time-efficiency and transferability between settings. The Edmonton Frailty Scale (EFS) is heralded as an effective tool capturing multi-dimensional aspects of frailty. Due to the lack of blanket referral system for some Multi-Disciplinary Team (MDT) members in our Irish rehabilitation hospital, early identification of frailty is key to ensure timely input from all disciplines. To optimise MDT intervention, the EFS was piloted alongside the CFS comparing user-experience and sensitivity. Methods: Education sessions were held by frailty-group members to familiarise staff with frailty concepts and frailty-tool administration. The EFS and CFS were administered with all patients over 65 years within 72 hours of admission onto two wards of our hospital over a three-month period. Frailty scale completion was co-ordinated by the physiotherapists and occupational therapists who operate a blanket referral system. Detection of frailty triggered an urgent referral to dietician, medical social work and speech and language therapy colleagues who don't operate a blanket referral system. The target time for MDT input was two days for the severely frail cohort and one week for mild or moderately frail patients. Results: The EFS was administered for 83 patients (mean age: 84 years). Of those, 6% were severely frail, 23% were moderately frail and 28% were mildly frail. The CFS was found to detect a higher frailty level in 47% of patients screened when compared to the EFS and took an average of ten minutes less to administer. Conclusion: The CFS will continue to be administered with patients due to its higher sensitivity to frailty and time efficiency for completion. Referrals will continue to be generated to all MDT members to expedite input with frail patients.